A Self-Compassion Module to Support Psychological Well-Being of Special Needs Teachers - Ulil Ester Bethania Gandhi Purba; Ika Andrini Farida (Psyche 165 Journal, 2025)
Special Education School (SLB) teachers encounter unique psychological challenges, including work stress, emotional exhaustion, and tendencies toward self-blame, when teaching children with special needs. This study aims to develop and evaluate a self-compassion module as an effort to strengthen teachers’ psychological well-being. Using a qualitative case study design, two teachers in Malang City participated: RH, an experienced teacher, and AR, a novice teacher. Data were collected through in-depth interviews, participant observation, and the Self-Compassion Scale (SCS). Pretest results indicated that RH scored at the medium level, while AR was at the low level. After completing the module intervention, both teachers’ scores improved to the high category. The module sessions considered most beneficial included reducing self-judgment, practicing mindfulness, journaling, and positive affirmations. Both participants reported significant changes, such as reduced self-criticism, improved emotional awareness, and greater resilience. These findings emphasize the role of self-compassion as a protective factor in maintaining teachers’ emotional health. The developed module holds potential as a practical tool for self-reflection, emotional regulation, and sustainable psychological support, though further refinement and testing with larger samples are recommended.